Root cation-exchange capacity and aluminum toxicity relationships in two pasture grasses - Fernandes, M. S.; Rossiello, R. O.P.; Arruda, M. L.R. (Pesquisa Agropecuaria Brasileira, 2014)
A study was made on the effects of AI levels (0, 0.75, 1.5,3 and 6 ppm Al) on Brachiaria decumbens and Cenchrus ciliaris, known to be tolerant and sensitive to Al, respectively. There was no difference in root length between the two grasses but Cenchrus showed a reduction in root volume as Al levels increased. Brachiaria showed a small increase in K and a great increase in Al content as Al levels increased while Cenchrus showed reduction in K, increase in Ca, and small increase in Al levels. Both plants had a decrease in root cation-exchange capacity (CEC) under 0 to 1.5 ppm Al; after that, there was a stabilization of CEC levels around 8 to 10 meq/100 g. The CEC decrease in Cenchrus was linear and sharp from 0 to 0.75 ppm Al while in Brachiaria it occurred more slowly. In Brachiaria there was a negative correlation between CEC and K and Al accumulation, and a positive correlation between CEC and Ca accumulation. No such correlations were obtained for Cenchrus. The results suggest that at least for the tolerant species (Brachiaria) the blocking of CEC sites by Al favours K uptake over Ca uptake.